Impact of the serum thyroglobulin concentration on the diagnostics of benign and malignant thyroid diseases - Rink, Th.; Dembowski, W.; Schroth, H.-J.; Klinger, K. (Nuklearmedizin - NuclearMedicine, 2000)
Aim of this study is to evaluate new and controversially discussed indications for determining the thyroglobulin (Tg) level in different thyroid diseases to support routine diagnostics. Methods: The following groups were included: 250 healthy subjects without goiter, 50 persons with diffuse goiter, 161 patients with multinodular goiter devoid of functional disorder (108 of them underwent surgery, in 17 cases carcinomas were detected), 60 hyperthyroid patients with autonomously functioning nodular goiter, 150 patients with Hashimoto’s thyroiditis and 30 hyperthyroid patients with Graves’ disease. Results: The upper limit of the normal range of the Tg level was calculated as 30 ng Tg/ml. The evaluation of the collective with diffuse goiter showed that the figure of the Tg level can be expected in a similar magnitude as the thyroid volume in milliliters. Nodular tissue led to far higher Tg values then presumed when considering the respective thyroid volume, with a rather high variance. A formula for a rough prediction of the Tg levels in nodular goiters is described. In ten out of 17 cases with thyroid carcinoma, the Tg was lower than estimated with thyroid and nodular volumes, but two patients showed a Tg exceeding 1000 ng/ml. The collective with functional autonomy had a significantly higher average Tg level than a matched euthyroid group being under suppressive levothyroxine substitution. However, due to the high variance of the Tg values, the autonomy could not consistently be predicted with the Tg level in individual cases. The patients with Hashimoto’s thyroiditis showed slightly decreased Tg levels. In Graves’ disease, a significantly higher average Tg level was observed compared with a matched group with diffuse goiter, but 47% of all Tg values were still in the normal range (< 30 ng/ml). Conclusion: Elevated Tg levels indicate a high probability of thyroid diseases, such as malignancy, autonomy or Graves’ disease. However, as low Tg concentrations cannot exclude the respective disorder, a routine Tg determination seems not to be justified in benign thyroid diseases.
Keywords: Thyroglobulin; nodular goiter; autonomy; thyroid carcinoma; Hashimoto’s thyroiditis; Graves’ disease